If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8+6h-4=80-4
We move all terms to the left:
8+6h-4-(80-4)=0
We add all the numbers together, and all the variables
6h+8-4-76=0
We add all the numbers together, and all the variables
6h-72=0
We move all terms containing h to the left, all other terms to the right
6h=72
h=72/6
h=12
| (-5x-1*2x^2)=(2x^2) | | 1.3(3.1r-10,4)=16 | | 4(x+9=20 | | 12x+15x=45 | | 72=2x6x=12x | | 7x+4+10x–7=14–23x+16–7x | | y=4L+3 | | 5/6=60/x | | 4x^2+48=4x+24+4x^2-8x | | 4d-5=50-7 | | y=50+2 | | p×72=2232 | | .80n=5.50 | | m-45=203.4 | | 3+4f=15 | | 3x+135=12x-9 | | -7(w-6)=-3w+46 | | x^2+4x-18=240 | | 2x0.5= | | 3u+3=-9 | | 5x+10=3(x-10) | | 2(3t-)+t=30-t | | 42.5+y=112.75 | | 627.90=42(x+) | | 8-3(x-4=4 | | s/30=112 | | 72=6(m+3.4) | | -3(2-r)=15 | | 6+2m-4=6m+8-2m | | 28(x-1)=-7(4-x)+2x | | 4272=48(p+15) | | 1980=36(p+15) |